2020
DOI: 10.1021/acs.iecr.9b06816
|View full text |Cite
|
Sign up to set email alerts
|

Novel N/Carbon Quantum Dot Modified MIL-125(Ti) Composite for Enhanced Visible-Light Photocatalytic Removal of NO

Abstract: Highly efficient and stable photocatalysts were synthesized at room temperature by modifying MIL-125(Ti) with N-doped carbon quantum dots (N/CM(Ti)). The N/ CM(Ti) with 2.5 vol % N doped carbon quantum dots (N/CQDs) had the best light absorption and visible-light photocatalytic nitrogen oxide (NO) removal efficiency (approximately 49%). It was found through X-ray photoelectron spectroscopy analysis that a N−Ti−O bond was formed in the 2.5 vol % N/CM(Ti), which is more conducive to charge transfer. Photocurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…synthesized a composite MIL-125­(Ti)/N-CQD as N/CM­(Ti) at room temperature and shows NO removal under visible-light with ∼49% efficiency. Figure c shows the NO removal with different catalysts as control MIL-125­(Ti) and different loaded N-CQD in N/CM­(Ti) composite . Huang et al reported the NOx removal and NO 2 production using photocatalyst CQD/ZnFe 2 O 4 composite that has significantly better activity (∼8 times) than that of ZnFe 2 O 4 because of rapid charge transfer and generation of reactive species (O 2 •– and • OH) under irradiation of visible light (λ > 420 nm) as shown in Figure d,e .…”
Section: Photocatalytic Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…synthesized a composite MIL-125­(Ti)/N-CQD as N/CM­(Ti) at room temperature and shows NO removal under visible-light with ∼49% efficiency. Figure c shows the NO removal with different catalysts as control MIL-125­(Ti) and different loaded N-CQD in N/CM­(Ti) composite . Huang et al reported the NOx removal and NO 2 production using photocatalyst CQD/ZnFe 2 O 4 composite that has significantly better activity (∼8 times) than that of ZnFe 2 O 4 because of rapid charge transfer and generation of reactive species (O 2 •– and • OH) under irradiation of visible light (λ > 420 nm) as shown in Figure d,e .…”
Section: Photocatalytic Applicationsmentioning
confidence: 94%
“…(c) MIL-125­(Ti) and N/CM­(Ti) composites with 0.25, 2.5, and 5.0 vol % loading of N/CQD under visible light. Reproduced from ref . Copyright 2020 American Chemical Society.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
“…Nitrogen oxides (NOx) have varying degrees of toxicity to human health and natural environment, and have become an increasingly serious global problem [49] . Chen and co‐workers [50] constructed highly efficient and stable photocatalysts by modifying MIL‐125 (Ti) with N‐doped carbon quantum dots (CDs@MIL‐125 (Ti)) for photocatalytic removal of NO (Figure 4b). Under light conditions, CDs@MIL‐125 (Ti) photocatalysts can catalyze NO to produce nitrate (NO 3 − ) and visible‐light photocatalytic nitrogen oxide (NO) removal efficiency (approximately 49%).…”
Section: Application Of Cds@mofs Composites In Photocatalysismentioning
confidence: 99%
“…Adapted from reference [48] with permission, copyright 2018 Elsevier. (b) A schematic illustration of N/CQDs/MIL-125(Ti) composite for photocatalytic removal of NO.Adapted from reference[50] with permission, copyright 2020 American Chemical Society.…”
mentioning
confidence: 99%
“…In the photocatalytic reaction over MIL-125 (Ti). Reproduced with permission [143]. Copyright 2020, American Chemical Society.…”
mentioning
confidence: 99%